Apparatus with one or more particular functions for connection to the British Telecommunications public switched telephone network. Apparatus with auto-calling, auto-answering and auto-clearing facilities. Specification for auto-calling facilities Part 3.1, (15th March 1985) - British Standards Institution,
No abstract available